Medical ICU Admission Diagnoses and Outcomes in Human Immunodeficiency Virus–Infected and Virus–Uninfected Veterans in the Combination Antiretroviral Era - Akgün, Kathleen M. (Crit Care Med, 2013)
OBJECTIVES: Human immunodeficiency virus (HIV)–infected (HIV+) patients on combination antiretroviral therapy are living longer but have increased risk for aging-associated disease which may lead to increasing critical care requirements. We compare medical ICU admission characteristics and outcomes among HIV infected and demographically similar uninfected patients (uninfected) and considered whether an index which combines routine clinical biomarkers (the Veterans Aging Cohort Study Index) predicts 30-day medical ICU mortality. DESIGN: Observational data analyses (Veterans Aging Cohort Study). SETTING: Eight Veterans Affairs medical centers nationwide. PATIENTS: HIV infected and uninfected with a medical ICU admission between 2002 and 2010. INTERVENTION: None. MEASUREMENTS AND MAIN RESULTS: Medical ICU admission was determined using bedsection (Veterans Affairs) and revenue center codes (Medicare). For Veterans Affairs admissions, we used clinical data to calculate Veterans Aging Cohort Study Index scores and multivariable logistic regression to determine factors associated with 30-day mortality. Overall, 539 of 3,620 (15%) HIV infected and 375 of 3,639 (10%) uninfected had a medical ICU admission; 72% and 78%, respectively, were Veterans Affairs based. HIV+ patients were younger at admission (p < 0.0001). Although most HIV+ patients were on antiretroviral therapy (71%) with undetectable HIV-1 RNA (54%), compared with uninfected they were more commonly admitted with respiratory diagnoses or infections (21% vs. 12%), were more likely to require mechanical ventilation (17% vs. 9%; p = 0.001), and had a higher mortality rate (18.6% vs. 11.2%, p = 0.003). Cardiovascular diagnoses were less common among HIV infected (18% vs. 29%; p < 0.0001). In logistic regression (c-statistic 0.87), a 5-point increment in Veterans Aging Cohort Study Index was associated with an odds ratio of death of 1.22 (95% confidence interval 1.14–1.30) among HIV infected and of 1.50 (95% confidence interval 1.29–1.76) among uninfected; infection/sepsis and respiratory diagnoses were also associated with mortality. CONCLUSIONS: Medical ICU admission was frequent, 30-day mortality higher, and mechanical ventilation more common in HIV infected compared with uninfected. The Veterans Aging Cohort Study Index calculated at medical ICU admission predicted 30-day mortality for HIV infected and uninfected. As more individuals age with HIV, their requirements for medical ICU care may be greater than demographically similar uninfected individuals.